Development of single step drilling technology for multilayer metallic-composite stacks using uncoated and PVD coated carbide tools. (January 2018) - Kuo, C.L.; Soo, S.L.; Aspinwall, D.K.; Carr, C.; Bradley, S.; M'Saoubi, R.; Leahy, W.
Abstract: The paper details experimental trials to evaluate the performance of uncoated and PVD coated tungsten carbide twist drills, for single shot drilling of 3-layer metallic-composite stack workpieces. A full factorial experiment was undertaken involving variations in feed rate (0.05 and 0.08 mm/rev) and drilling strategy (with and without pecking cycle), in addition to the tool coating (TiAlN/TiN). All of the uncoated drills machined 180 holes without exceeding the flank wear criterion of 0.3 mm, regardless of feed rate level or drilling strategy. In contrast, tool life for the coated drills was ∼20-50% lower (90–148 holes). Thrust force decreased by ∼12% when operating at the higher feed rate while use of coated drills led to an increase of up to 18% due to the larger cutting edge radius. Conversely, the hard/ceramic coating provided greater wear resistance at the peripheral corner of the drill resulting in lower torque (up to ∼10%) compared to the uncoated tool. Furthermore, holes produced utilising the TiAlN/TiN coated drills typically exhibited superior geometrical accuracy in terms of diameter, out of roundness and cylindricity. Drilling at the lower feed rate of 0.05 mm/rev however generated larger exit burrs by up to ∼90%.